Notes on the genus Homogryllacris Liu, 2007 (Orthoptera: Gryllacrididae: Gryllacridinae) with description of two new species from China - Du, Baojie; Bian, Xun; Shi, Fuming (Zootaxa, 2016)
Two new species of the genus Homogryllacris Liu, 2007 are described and illustrated, i.e. Homogryllacris brevipenna sp. nov. (type locality: Yunnan), Homogryllacris curvicauda sp. nov. (type locality: Guangxi). A key to the species, additional bionomics and a distribution map for the genus Homogryllacris are provided. All material examined is deposited in the Museum of Hebei University.